2016
DOI: 10.3892/etm.2016.3828
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of carbapenemases among high-level aminoglycoside-resistant Acinetobacter baumannii isolates in a university hospital in China

Abstract: The prevalence of aminoglycoside resistant enzymes has previously been reported and extended-spectrum β-lactamase among Acinetobacter baumannii. To track the risk of multidrug-resistant A. baumannii, the present study aimed to determine the prevalence of carbapenemases in high-level aminoglycoside resistant A. baumannii over two years. A total of 118 strains of A. baumannii were consecutively collected in the First Affiliated Hospital of Chengdu Medical College, Chengdu, China. These isolates were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 58 publications
4
14
2
Order By: Relevance
“…In this study, we observed that 4 out of 33 strains with HLAR phenotype were lacking the 16S rRNA methylase genes. Similar finding was also reported in a study conducted in China by Wang et al [24] on Acinetobacter baumannii strains. Moreover, they showed that some strains with HLAR phenotype had genes encoding AMEs instead of the 16S rRNA methylase genes.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we observed that 4 out of 33 strains with HLAR phenotype were lacking the 16S rRNA methylase genes. Similar finding was also reported in a study conducted in China by Wang et al [24] on Acinetobacter baumannii strains. Moreover, they showed that some strains with HLAR phenotype had genes encoding AMEs instead of the 16S rRNA methylase genes.…”
Section: Discussionsupporting
confidence: 91%
“…Our previous surveys revealed that the antibiotic resistance among A. baumannii clinical isolates is very serious. [ 20 , 21 ]. And antimicrobial- resistant A. baumannii has very high potential to spread among ill patients in ICU (intensive care units), so it is crucial to adopt early recognition and timely implementation of appropriate infection control measures in preventing outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…Ten 16S-RMTase gene-negative strains showing a high MIC (>1,024 mg/L) for kanamycin carried at least one aac(3)-IId or aph(3´)-Ia gene, indicating that aac(3)-IId and aph(3´)-Ia may provide high-level resistance against kanamycin. Similarly, the production of 16S-RMTase or a combination of multiple AMEs was shown to be the major mechanism underlying high-level aminoglycoside-resistant gram-negative bacilli in Chengdu, China, and Brazil ( Wang et al, 2016 ; Ballaben et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%